Symmetry-Adapted Perturbation Theory Applied to Endohedral Fullerene Complexes: A Stability Study of H2@C60 and 2H2@C60 - Korona, Tatiana; Heßelmann, Andreas; Dodziuk, Helena (Journal of Chemical Theory and Computation, 2009)
Because of difficulties in a description of host-guest interactions, various theoretical methods predict different numbers of hydrogen molecules which can be inserted into the C60 cavity, ranging from one to more than 20. On the other hand, only one H_2 molecule inside the C60 fullerene has been detected experimentally. Moreover, a recently synthesized H_2@C70 complex prevails in the mixture formed with 2H_2@C70. To get a deeper insight into the stability of the complexes created from C60 and hydrogen molecules, we carried out highly accurate calculations for complexes of one or two hydrogen molecules with fullerene applying symmetry-adapted perturbation theory (SAPT) and a large TZVPP basis set for selected points on the potential energy surfaces of H_2@C60 and 2H_2@C60. The electron correlation in the host and guests has been treated by density functional theory. Our calculations yield the stability of the recently synthesized H_2@C60 complex. In addition, for all tried positions of the H_2 dimer inside the C60 cage, the 2H_2@C60 complex has been characterized by a positive interaction energy corresponding to the instability of this species. Contrary to the conclusions of several theoretical studies, this finding, as well as model considerations and literature experimental data, indicates that only one hydrogen molecule can reside inside the C60 cage. The calculated energy components have been analyzed to identify the most important contributions to the interaction energy. Supermolecular interaction energies obtained with MP2, SCS-MP2, and DFT+Disp methods are also reported and compared to those of DFT-SAPT. The DFT-SAPT interaction energy has also been calculated for several points on the potential energy surface for a larger 2H_2@C70 complex, confirming, in agreement with recent experimental findings, that this species is stable. The DFT-SAPT approach has been used for the first time to obtain interaction energies for van der Waals endohedral complexes, demonstrating that the method is capable of handling such difficult cases.
EAM Import::2019-03-12